(untitled) (Research, Society and Development, 2021)
The avocado (Persea americana Mill.) Is a fruit that is originally from Central America, and it has a high nutritional value. The pulp is the most widely consumed in the form of dessert, salads, sauces and cosmetics. Several studies report that avocado pulp oil has a high concentration of unsaturated fatty acids that provide beneficial health effects. The oil was extracted from four avocado varieties (Quintal, Fortuna, Ouro Verde and Hass) by reflux using two solvents, methanol and hexane, to evaluate the fatty acid profile by GC-FID, as well as the antioxidant potential using several methods (elimination of DPPH radicals, bleaching of β-carotene, reducing power test and degradation of deoxyribose). The oils had a moderate moisture content, and the most expressive yield was obtained using hexane, mainly for the Quintal and Hass varieties. The percentage of the principal fatty acids varied according to the solvent used, but oleic, palmitic, linoleic, palmitoleic and linolenic acids were identified in all the oils. No antioxidant potential was observed for the oils by the methods used.